Cemeteries in Poland as Built Structures and Their Impact on Shaping the Social Environment - Marta Baranowska; Paweł Fiktus (Krytyka Prawa)
The research objective of this article is to analyse the legal aspects concerning the placement of cemeteries in urban space. It will aim to reconstruct legal definitions of cemeteries and to provide an answer to the research question concerning the Polish legal regulations on the impact of cemeteries on the shaping of the social environment. Analysis will be made of the location of other buildings within their boundaries, the impact of cemeteries on the use of property rights and economic activity in their vicinity as well as cemeteries as places of historical memory. The findings conclude that the Law on Cemeteries and Burial of the Dead is an outdated act subject to increasing criticism. While in the case of a cemetery, understood as a construction object, we are able to use the provisions of the construction law, in the case of defining its social dimension, this is unfortunately impossible.